The event of the political party - Pritchard, Gwynn; British Broadcasting Corporation. Television Service (Milton Keynes : Open University)
Regarding the events that occur in political parties
Converted into VHS 1/2 in.
Title from title screen
Executive producer, John Miller ; film editor, Des Murphy ; film cameraman, Peter Chapman, Ken Lowe, Tony pierre-Roberts
Narrator : Michael Smee
Keywords: Political parties; Political science